Does Caffeine Intake Increase the Incidence of Tinnitus? A Systematic Review - Aljuaid,Sattam M. (2021)
Abstract Introduction Excessive caffeine intake has been thought to be a contributory factor for tinnitus. However, there has been no systematic review to elucidate the causal relationship between caffeine intake and the incidence of tinnitus. Objectives We performed the current review aiming at evaluating the evidence from the current literature for the relationship between caffeine intake and the incidence of tinnitus. Data Synthesis Databases including PubMed, Scopus, and Google scholar were searched for relevant articles. A total of 142 studies were screened for eligibility, of which four articles met our inclusion criteria: two were prospective cohorts and two were cross-sectional studies. Although one study found no association between caffeine consumption and the incidence of tinnitus, an inverse relationship was reported by two population-based studies. Concerning patients with preexisting tinnitus, reduction of caffeine intake in a subset who consumed 150 ml to 300 ml/day of coffee yielded a favorable outcome in tinnitus severity. However, those with higher dose intake were less prone to have improvement in the severity of tinnitus. Conclusion Although the current review was inconclusive, it appears that the incidence of tinnitus in previously unaffected individuals might be prevented by a high dose of caffeine intake. However, in preexisting tinnitus, a high dose of caffeine may adversely interfere with the efficacy of caffeine reduction.